Comprehensive review on Schisandra chinesis - Sonal Bansal; Km Pratiksha; Rishabh Gaur; Somya Gupta; Ved Prakash Jadaun; Vibha Kumari (Elsevier, 2024)
Introduction: Schisandra chinensis, also known as Chinese magnolia vine, belongs to the family Schisandraceae. There are two types of fruit of Schisandra that differ in species: one is from S. chinensis, named Wuweizi, and the second belongs to S. sphenanthera, named Nanwuweizi. Both are native to the southern Chinese. Traditional Chinese Medicine (TCM) practitioners used plants for the treatment of cancer. The experiment shows that the extract of the berry is effective against gram-positive and gram-negative bacteria and used as traditional medicine in southeast Asia and Russia for the treatment of cardiovascular and GI diseases. Flavonoids, tannins, triterpenoids, and Schistantherin A are the major phytoconstituents. Methodology: Data was collected from online databases including Google Scholar, Scopus, PubMed, and Web of Science and searched using different keywords: S. chinensis phytochemistry and Schistantherin A. The prime objective of this review was to provide previously reported information such as pharmacological activity and toxicity about the Chinese plant species. Result: According to our research, S. chinensis contains a variety of physiologically active compounds, including terpenoids, tannins, flavonoids, and schistantherin A. Additionally, previous studies have demonstrated the significant pharmacological action of fruit extracts and shows anti-diabetic, antioxidant, hepatoprotective, and anti-cancer effects. Discussion: The following research indicates that S. chinensis has a great potential for facilitating the creation of preventative as well as medicinal products and supplements for cancer, hypertension, asthma, diabetes, and other disorders. Chinese magnolia vine is a safe and effective plant for human consumption. As such, it should be incorporated in food intakes and as an active ingredient in medicinal formulations. Conclusion: S. chinensis is a good source of phytoconstituents that may be added to food and have the potential to treat a variety of mild to serious medical ailments. Other scientists will be motivated to investigate the chosen plant species further as a result of this assessment, especially in the areas of toxicity and biologically active